مستوى تقدير طلبة برنامج التربية العملية لدور المعلمين المتعاونين في تنمية مهاراتهم التدريسية (دراسة ميدانية على عينة من الطلبة في كلية العلوم التربوية في الأردن) - عايش احمد (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدفت هذه الدراسة إلى معرفة دور المعلمين المتعاونين في تنمية مهارات طلبة كلية العلوم التربوية التدريسية، كما حاولت معرفة دلالة الفروق في وجهات نظر الطلبة المعلمين تجاه هذا الدور، وفقا للجنس، وقد تألفت عينة الدراسة من (82) فردا من الجنسين،وقد اتبع الباحث المنهج الوصفي التحليلي في الدراسة ، بالاعتماد على أداة قياس مؤلفة من (34) فقرة، موزعة على مجالي التخطيط والتنفيذ ، وقد أظهرت نتائج الدراسة ، أن مستوى تقدير الطلبة في كلية العلوم التربوية لدور المعلمين المتعاونين في تنمية مهاراتهم التدريسية في مجال التنفيذ والتقويم ، جاء جيدا على أداة الدراسة ككل ، في حين أظهرت النتائج اختلافا في وجهات نظر الطلبة على المجالات منفردة ، فجاءت استجابات عينة الدراسة من الإناث على فقرات مجال التنفيذ جيدة جدا، في حين جاء المستوى جيداً عند عينة الدراسة من الذكور، ولم تظهر الدراسة اختلافا في تقديرات الطلبة من الجنسين لدور المعلمين المتعاونين في تنمية مهاراتهم التدريسية في مجال التقويم، إذ جاءت جيدة ،وأظهرت الدراسة وجود فروق ذات دلالة إحصائية في مجال التنفيذ عند مستوى (α = 0.05) بين درجات الذكور والإناث، لصالح الإناث. This study aimed to identify the role of cooperating teachers in improving UNRWA Faculty of Educational Sciences practicum programme student teachers’ teaching skills. The study also tried to investigate whether there are differences in the students’ views of the cooperating teachers’ role that are attributed to gender. The study sample consisted of (82) male and female students divided equally to both sexes. The descriptive analytical approach was employed making use of a survey questionnaire consisting of (34) items distributed among two domains: planning and implementation. The results of the study showed that the degree of Faculty of Educational Sciences students’ appreciation of the role of cooperating teachers in improving their teaching skills across the items of the whole questionnaire in both the implementation and evaluation domain was good. While the results showed a difference in students’ views of individual domains. The females’ responses on the items related to implementation were very good, while the males’ responses on the same items were good. Moreover, the study showed no difference in the estimates of students of both sexes for the role of cooperating teachers in improving their teaching skills in the evaluation domain as they ranked good. The results of the study also revealed that there were statistically significant differences at (α=0.05) in the implementation domain between the males and females’ estimates in favour of the females.